Non-enzymatic Transformation of Aflatoxin B1 by Pseudomonas geniculata m29 - Yao, Yuanyuan; Shu, Xian; Wang, Dongdong; Kan, Wenjie; Su, Pengfei; Hu, Hao; Chen, Xu; Wang, Dacheng; Huang, Shengwei; Wu, Lifang (Frontiers in Microbiology, 2021)
Aflatoxin B1 (AFB1) is the most harmful mycotoxin produced by filamentous fungi and presents a serious threat to human and animal health. Therefore, it is essential to protect humans and animals from AFB1-induced acute and chronic toxicity. In this study, Pseudomonas strain m29 having a high efficiency of AFB1 transformation was isolated from soil. The transformation ratio by m29 was more than 97% within 24 hours, and the optimum temperature for transformation was 37 °C. Moreover, the AFB1 transforming activity was mainly attributed to the cell-free supernatant of strain m29. The metabolite that plays a crucial role in AFB1 transformation is likely 1,2-dimethylhydrazine or 1,1-dimethylhydrazine, as identified by GC-MS and LC-MS analysis. AFB1 was transformed into a product with molecular formula C17H14O7. To the best of our knowledge, this is the first study of non-enzymatic AFB1 transformation by bacteria. Importantly, this AFB1 transformation mechanism could be universal to various microorganisms.